Pengembangan Simulasi Sinyal Radar Dan Proses Interleaving Sebagai Inputan Pada Radar Detector - Norma Ningsih (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2017)
In modern warfare that use electronics, many developed radar signal detection system. Radar is an object detection object that uses radio wave to detect, to determine the distance and to measure the speed of an object. In order to develop a radar detector that can detect radar system in accordance with the parameters of the transmitted radar signal in the form of Pulse Descriptor Word (PDW), we need a simulator that can produce a wide range of radar signal characteristics in accordance with the actual characteristics of the radar signal characteristics.Including the function to outwit radar detector, a way to simulate various types of PRI and frequency (hopping and agility). The signals emitted by multiple radars will be received at the receiver in a state of overlapping (interleaving) in accordance with less value Time Of Arrival (TOA) and the PRI of each radar signal. On the receiving side, namely radar detector, signal suffered back interleaving will be described by analyzing the parameters of PRI of radar signals using sequence search method. It is intended that the receiver can recognize whether the signal came from enemy radar or not. By using sequnce search, the received signal at the radar detector can be separated according to the value that the PRI. PRI is entered with a value of 1 s, 1.4 μs and 2.23μs.